O erotismo em "Felicidade Clandestina". "As Águas do Mundo", "O Menino" e "As Cerejas" : diálogos entre Clarice Líspector e Lygia Fagundes Telles - Novaes, Nayara Marylandy Saraiva (2017)
Our research analyzes, through the reading and later comparison of the narratives, the thematic confluence of eroticism, in the short stories “Felicidade Clandestina” and “As Águas do Mundo” the literary work of Felicidade Clandestina (launched in 1971), by Clarice Lispector, and in the short stories “As cerejas”, of the literary work Seleta (launched in 1971), and “O Menino”, published in the literary work O Cacto Vermelho (from 1949, and later included in Antes do Baile Verde, from 1970), by Lygia Fagundes Telles. The intention is to relate the eroticism to the uncovered of the universe of female characters, probing, in these works, the way by which if sculpts the feminine sexuality, using, for this reason, the analysis of language - or languages - used. In addition, we want to investigate the search process of identity assertion of female characters, demonstrating the relevance of eroticism for evolution of the plot of the investigated works and for the development of the profile of the characters, pointing the theme as one of the mechanisms for better understanding of the condition of women and of human existence itself. In order to achieve the objectives presented, we use a research of a reflexive and bibliographical nature, dealing with an interpretative study of the literary text, originating from structured knowledge about the genre short story and the theme of eroticism.